2022
DOI: 10.1093/mnras/stac2358
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde binding energies: a coupled experimental and theoretical study

Abstract: Acetaldehyde is one of the most common and abundant gaseous interstellar complex organic molecules, found in cold and hot regions of the molecular interstellar medium. Its presence in the gas-phase depends on the chemical formation and destruction routes, and its binding energy (BE) governs whether acetaldehyde remains frozen onto the interstellar dust grains or not. In this work, we report a combined study of the acetaldehyde BE obtained via laboratory TPD (Temperature Programmed Desorption) experiments and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 88 publications
2
13
0
Order By: Relevance
“…Although most of the molecules desorb in the “trapped” peak, the eventual appearance of the “volcano” TPD peak at higher laser fluence indicates that the molecule’s interaction with water is not too strong. This fits with the assignment to acetaldehyde, which can form one hydrogen bond with water, but still prefers to form clusters at the interface when deposited on water–ice surface . Some hydrogen bonds are formed between water and acetaldehyde resulting in the codesorption of the two molecules.…”
Section: Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although most of the molecules desorb in the “trapped” peak, the eventual appearance of the “volcano” TPD peak at higher laser fluence indicates that the molecule’s interaction with water is not too strong. This fits with the assignment to acetaldehyde, which can form one hydrogen bond with water, but still prefers to form clusters at the interface when deposited on water–ice surface . Some hydrogen bonds are formed between water and acetaldehyde resulting in the codesorption of the two molecules.…”
Section: Results and Discussionsupporting
confidence: 83%
“…This fits with the assignment to acetaldehyde, which can form one hydrogen bond with water, but still prefers to form clusters at the interface when deposited on water–ice surface. 53 Some hydrogen bonds are formed between water and acetaldehyde resulting in the codesorption of the two molecules. Acetaldehyde molecules that do not form hydrogen bonds with water due to unfavorable relative orientation are ejected in the “volcano” peak.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This fact could be inferred from previous studies (Garrod, R. T. et al 2007;Minissale, M. et al 2016;Fredon & Cuppen 2018;Fredon et al 2021) where the efficiency of chemical desorption is a function of BE. However, as previously indicated for thermal desorption studies Ferrero et al 2022a;Molpeceres, G. et al 2022), we must emphasize that considering the whole distribution of binding sites is essential to unravel the role of non-thermal mechanisms. Here we found that the binding energy anticorrelates with the fraction of energy dissipated into the lattice and the acquired translational energy of the nascent molecule.…”
Section: Extended Samplingmentioning
confidence: 89%
“…As pointed out by previous articles (Ferrero et al 2022;Minissale et al 2022;Tinacci et al 2022), attention should be given to the way in which the prefactor in the desorption rate (k thdes in Equation (1)) is computed. As in the aforementioned articles, we here adopt the Tait et al (2005) formula:…”
Section: The Desorption Rate Prefactormentioning
confidence: 99%